Investigating the intention and behavior of vegetable farmers to adopt IoT technology: survey—based evidence from China - Li, Lianying; Zhang, Mingzhu; Chandio, Abbas Ali; Liu, Yan (Frontiers in Sustainable Food Systems, 2024)
A key instrument for upgrading China’s agriculture is the Internet of Things (IoT). To solve the problem of IoT technology promotion, farmers’ intentions to adopt IoT technology must be transformed into behavior, and their intentions and behaviors must be unified. The multivariate logistic model was used to analyses the factors influencing farmers’ intention to adopt IoT technology and behavioral deviation based on survey data of vegetable farmers in Jiangxi Province. The ISM model was used to investigate the relationship and hierarchy between the factors influencing farmers’ intention to adopt IoT technology and behavioral deviation. The findings revealed that first, a significant deviation exists between vegetable farmers’ IoT technology adoption intention and behavior, with 72.69% of those surveyed having the intention to adopt, but did not follow through. Second, among the 12 factors confirmed as remarkably influencing the deviation, expected return is the most superficial factor; intermediate influencing factors include vegetable price volatility, adoption cost, credit support, related knowledge and skills, and technology maturity; secondary factors include social capital, whether vegetables are registered trademarks, planting scale, planting method, and IoT related equipment supply; and age is the deepest root factor.